Village Status Grouping Analysis Using Agglomerative Hierarchical Clustering (AHC): Village Status Grouping Analysis Using Agglomerative Hierarchical Clustering (AHC) - Paska Marto Hasugian (Institute of Computer Science (IOCS), 2020)
increasing the standard of living of the community, both materially and spiritually. Careful development planning can create a development that is right on target. One of the supporting aspects of development planning is the availability of detailed data at the smallest area level. Information to the smallest area can be used as a guide in making policies that are more targeted. The village as a government that is directly in contact with the community is the main focus in government development, this is because most of Indonesia's territory is in rural areas which are directly under the auspices of the PDTT Ministry (Ministry of Villages, Disadvantaged Village Development, and Transmigration), to carry out their duties and The responsibility for village development has been assessed in establishing a village classification based on the building village index to convert an underdeveloped village into a developed or independent village which is assessed based on certain sectors through a very long and certainly sustainable process. Determination of classification is based on the village index value build (IDM) based on the average Ecological Resilience Index (IKL), Economic Resilience Index (IKE), and Social Resilience Index (IKS). From the IDM value, the villages will be classified in the status of villages namely independent villages, Advanced, Developing, Underdeveloped, and Very Underdeveloped